TRANSFORMASI BISNIS KREATIF MICRO ENTERPRENEUR DALAM MEMPERTAHANKAN OMSET DI MASA COVID-19 - Rofiq, Mohammad As’adur; An Nawawi, Muhammad Afif; Syafitri, Rizky Intan; Ektiarnanti, Riska; Maenadi, Debi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This article discusses the impact of covid-19 on microbusinesses and their strategies for maintaining turnover through changes to the creative business model of the digital era. The appeal for large-scale social restrictions resulted in the cessation of tourism sector activities which had a direct impact on nearby micro entrepreneurs. The research method used is descriptive qualitative with observation techniques. Researchers try to collect data and describe the phenomena that occur at the Bung Karno Museum tourist attraction. Based on research, it is known that due to the Covid-19 pandemic, the area must be completely closed during the PSBB. Micro entrepreneurs such as food, craft, distro and mini cafes have decreased their turnover by 30-100 percent because there are no tourists visiting. There are only a few traders who make changes to the digital business model. On average, they still use the old method by only relying on consumers to buy their products directly. The results of this study recommend strategies to maintain turnover for micro businesses to carry out digital trade transformation through websites, social media and marketplaces as well as to improve product attributes by paying attention to quality and creative packaging design in order to attract consumers. These changes are expected to expand market share and be able to maintain turnover during the pandemic as well as be able to adapt to changes in the digital era business environment.